PENGARUH LITERASI KEUANGAN SYARIAH, PENGALAMAN KEUANGAN, DAN ETIKA KONSUMSI TERHADAP PERILAKU KEUANGAN PEDAGANG PASAR TRADISIONAL - Kikin Mutakin; Ihrom Jaelani; Acim Acim (KHITABAH: Khazanah Penelitian Perbankan Syariah, 2025)
This study aims to analyze the influence of Islamic financial literacy, Islamic financial experience, and self-control on Islamic financial behavior in traditional market traders. The background of this study is the challenges faced by traditional business actors amidst the rapid digitalization of the economy and the low level of Islamic financial literacy and inclusion in Indonesia. With a quantitative approach, this study uses a multiple linear regression method on 50 market trader respondents selected purposively. The results of the analysis show that simultaneously, the three independent variables do not have a significant effect on Islamic financial behavior (sig. F value > 0.05). Likewise, partially, Islamic financial literacy, Islamic financial experience, and self-control do not have a significant effect on Islamic financial behavior. This indicates that there are other factors outside the model that may be more dominant in shaping Islamic financial behavior, such as religious understanding, local cultural values, or the influence of the social environment. This study recommends the need for a deeper educational and spiritual approach and community-based economic assistance programs to strengthen Islamic financial practices at the micro level